Different clinical phenotypes of persistent post-traumatic headache exhibit distinct sensory profiles. (June 2020) - Levy, Dan; Gruener, Hila; Riabinin, Miri; Feingold, Yelena; Schreiber, Shaul; Pick, Chaim G; Defrin, Ruth
Introduction: Persistent post-traumatic headache remains a poorly understood clinical entity. Although there are currently no accepted therapies for persistent post-traumatic headache, its clinical symptoms, which primarily resemble those of migraine or tension-type headache, often serve to guide treatment. However, evidence-based justification for this treatment approach remains lacking given the paucity of knowledge regarding the characteristics of these two major persistent post-traumatic headache phenotypes and their etiology. Methods: We compared clinical features and quantitative sensory testing profiles between two distinct cohorts of persistent post-traumatic headache subjects that exhibited symptoms resembling either migraine (n = 15) or tension-type headache (n = 13), as well as to headache-free subjects that had suffered traumatic brain injury (n = 19), and to healthy controls (n = 10). We aimed to determine whether the two persistent post-traumatic headache subgroups could be discriminated based on additional clinical features, distinct quantitative sensory testing profiles, or the interaction of pain severity with the level of post-traumatic stress disorder. Results: Persistent post-traumatic headache subjects with migraine-like symptoms reported that bright light and focused attention aggravated their pain, while stress and nervousness were reported to aggravate the headache in subjects with tension-type headache-like symptoms. Quietness was better in alleviating migraine-like persistent post-traumatic headache, while anti-inflammatory medications provided better relief in tension-type headache-like persistent post-traumatic headache. The two persistent post-traumatic headache subgroups exhibited distinct quantitative sensory testing profiles with subjects exhibiting tension-type headache-like persistent post-traumatic headache displaying a more pronounced cephalic and extracephalic thermal hypoalgesia that was accompanied by cephalic mechanical hyperalgesia. While both persistent post-traumatic headache subgroups had high levels of post-traumatic stress disorder, there was a positive correlation with pain severity in subjects with tension-type headache-like symptoms, but a negative correlation in subjects with migraine-like symptoms. Conclusions: Distinct persistent post-traumatic headache symptoms and quantitative sensory testing profiles may be linked to different etiologies, potentially involving various levels of neuropathic and inflammatory pain, and if confirmed in a larger cohort, could be used to further characterize and differentiate between persistent post-traumatic headache subgroups in studies aimed to improve treatment.